Study on the interaction between β-carotene and gut microflora using an in vitro fermentation model - Zhixian Li; Zhuqing Dai; Enjuan Shi; Peng Wan; Guijie Chen; Zhongyuan Zhang; Yayuan Xu; Ruichang Gao; Xiaoxiong Zeng; Dajing Li (Food Science and Human Wellness)
β-Carotene, a typical non-oxygenated carotenoid, is the most efficient source of retinol (VA). The low bio-availability of β-carotene lead to large accumulation in colon; however, the relationship between β-carotene and gut microflora remains unclear. This study intends to explore the interaction between β-carotene and gut microflora using an in vitro fermentation model. After 24 h fermentation, the degradation rate of β-carotene was (64.28 ± 6.23)%, which was 1.46 times that of the group without gut microflora. Meanwhile, the production of VA was nearly 2 times that of the group without gut microflora, indicating that the gut microflora can metabolize β-carotene into VA. β-Carotene also influences the production of short-chain fatty acids (SCFAs), the production of total SCFAs in 0.5 mg/mL β-carotene (BCM) group was (44.00 ± 1.16) mmol/L, which was 2.26 times that of the blank control (BLK) group. Among them, the production of acetic acid in BCM group was (19.06 ± 0.82) mmol/L, which was 2.64 time that of the BLK group. Furthermore, β-carotene significantly affected the structure and composition of gut microflora, increasing the abundance of Roseburia, Parasutterella and Lachnospiraceae, and decreasing the abundance of Dialister, Collinsella and Enterobacter (P < 0.05). This study provides a new way to understand how β-carotene works in human body with gut microflora.